Acute/Chronic Responses of Combined Training on Serum Pro-thermogenic/Anti-inflammatory Inducers and Its Relation With Fed and Fasting State in Overweight Type 2 Diabetic Individuals - Bonfante, Ivan Luiz Padilha; Duft, Renata Garbellini; Mateus, Keryma Chaves da Silva; Trombeta, Joice Cristina dos Santos; Finardi, Enrico Antonio Rautenberg; Ramkrapes, Ana Paula Boito; Brunelli, Diego Trevisan; Mori, Marcelo Alves da Silva; Chacon-Mikahil, Mara Patricia Traina; Velloso, Licio Augusto; Cavaglieri, Cláudia Regina (Frontiers in Physiology, 2022)
Concentrations of pro-thermogenic/anti-inflammatory inductors are influenced by fed/fasting, sedentary/trained states, and metabolic pattern. However, there is a lack of information on the interactions of these conditions, especially in humans. Thus, the present study aimed to evaluate the chronic and acute training responses as well as the fed/fasted states of serum pro-thermogenic/anti-inflammatory inducers in overweight type 2 diabetics individuals. 15 type 2 diabetic individuals (BMI: 29.61 ± 3.60 kg/m2; age: 50.67 ± 3.97 years) participated in the study. In the pre-and post-experimental periods, baseline clinical parameters analyses were performed. Pro-thermogenic/anti-inflammatory inductors were evaluated pre/post-baseline and before, shortly after, and after 30’ and 60’ in the first and last sessions of a 16-week combined training (CT) period. These inducers were also compared for fasting and feeding before and after the training period. CT has improved baseline physical fitness, metabolic pattern, and it has also increased IL33 and FNDC5/irisin. In the first training session, there was a decrease in IL4, IL13, and IL33, besides an increase in FNDC5/irisin, and natriuretic peptides. In the last training session, there was an increase in natriuretic peptides and BMP4. Differences in responses between the first and last training sessions were observed at certain post-session times for IL4, IL33, and natriuretic peptides, always with higher concentrations occurring in the last session. In evaluating the area under the curve (AUC) of the first and last training session, FNDC5/irisin, natriuretics peptides, and meteorin-like showed increase areas in the last training session. The pre-training fed state showed an increase in IL4 and IL33, while in fasting there was an increase in meteorin-like and natriuretic peptides. In the post-training, IL4 and IL13 were increased in the fed state, while meteorin-like and natriuretic peptides remained increased in the fast. Adaptation to physical training and a better metabolic pattern favor an improvement in the acute secretory pattern in part of pro-thermogenic and anti-inflammatory substances analyzed. The fed and fasting states also interfere differently in these substances, where fasting interferes with the increase of myokines, while the fed state induces an increase in interleukins.